2008
DOI: 10.1515/sg-2008-0015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Genetic Structure Assessed by Amplified Fragment Length Polymorphism and Retrotransposon-based Sequence-specific Amplification Polymorphism for Portuguese Populations of Pinus pinea L.

Abstract: In order to assess genetic diversity within and among populations of Pinus pinea L. (stone pine), seven Portuguese populations originating from three Provenance Regions were selected and genotyped using two marker systems. We compared the genetic variation of these populations using retrotransposon-based sequence-specific amplification polymorphism (SSAP) and amplified fragment length polymorphism (AFLP). In total, 105 trees were screened with three primer enzyme combinations (PEC), producing 232 SSAP and 132 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Nasri et al (2005) studied fatty acids of seeds in French and Turkish provenances, and the low genetic diversity detected was attributed to the homogeneity of the reproductive material due to the human-induced species propagation. Likewise, Evaristo et al (2008) indicated a lack of differentiation between provenances in relation with growth.…”
Section: Introductionmentioning
confidence: 99%
“…Nasri et al (2005) studied fatty acids of seeds in French and Turkish provenances, and the low genetic diversity detected was attributed to the homogeneity of the reproductive material due to the human-induced species propagation. Likewise, Evaristo et al (2008) indicated a lack of differentiation between provenances in relation with growth.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that retrotransposons are excellent markers for taxonomic analysis, going as far as elucidating evolutionary relationships between plant species [86]. Stone pine retrotransposons provide taxonomic identifications more closely aligned with morphological data than other genome fragment analysis [25]. This fact illustrates the importance of these sequences for the validation of taxonomic identification.…”
Section: Retrotransposonsmentioning
confidence: 95%
“…There was a 9-year period where no works were published on P. pinea's genome, revealing a lack of interest in this particular subject. Retrotransposon markers were used by Evaristo et al (2008) [25] to generate taxonomic data that are more consistent with morphological criteria than amplified fragment length polymorphism (AFLP)-based markers for P. pinea. Retrotransposon markers were more effective in determining population-specific genomic diversity than previous approaches based on polymorphic regions.…”
Section: Stone Pine Genomementioning
confidence: 99%
“…Similarly, average PY value (3.9%) is also within the range of historical values reported for Italy (3.6% [40,44] and Spain (2.7-4.4% [45]). However, the average PY value is higher than values reported for Europe after the arrival of L. occidentalis, which caused a drastic decrease in Spain (1.1-2.1% [31,45]) and Portugal (1.7% [46]; 3.0% [44]). In Chile, a trend towards PY decrease was also reported [23,47].…”
Section: Plos Onementioning
confidence: 96%